Anisotropy growth of perovskite crystal induced by layered double hydroxide for efficiency enhancement of solar cell. (10th January 2023) - Kong, Lingwei; Liang, Kaixiang; Wang, Ruixing; Liu, Jing; Shi, Wenying; Lu, Chao
Highlights: Micro and macro anisotropy of LDHs-NS guide the anisotropic growth of PVK crystals. Efficient charge transport and low trap-state density are achieved. The optimized device yields a significant enhancement in stability and PCE. Abstract: The anisotropy of perovskite (PVK) crystals is important for charge carrier transport and light absorption. In this regard, organic small molecules are most commonly used to induce the orientation growth of PVK. However, the high volatility and high diffusion coefficient of small molecules hinders its practical application. Here, inorganic layered double hydroxide nanosheets (LDHs-NS) is introduced into the PVK solution, where both micro and macro anisotropy of LDHs-NS guide the anisotropic growth of PVK crystals. Based on this, the efficiency of assembled perovskite solar cells (PSC) in an all-air environment can reach 12.26% with excellent thermal stability. The orderly arrangement of –OH on LDHs-NS surfaces can induce orderly growth of PVK crystals by interacting with Pb 2+ ; the anisotropy stacking of LDHs-NS ensured the orderly growth of PVK crystals on a large scale. Our work has important guiding implications for the anisotropy growth of PVK crystal, resulting in more efficient PSCs. Graphical abstract: In this paper, hydroxide nanosheets (LDHs-NS) is used as an additive to the perovskite absorbent layer, because the micro and macro anisotropic of LDHs-NS guides the anisotropic growth of perovskite crystals, the optimized device significantly improves stability and photoelectric conversion efficiency. Image, graphical abstract